2019
DOI: 10.1056/nejmoa1812406
|View full text |Cite
|
Sign up to set email alerts
|

Heart and Lung Transplants from HCV-Infected Donors to Uninfected Recipients

Abstract: Dr. Mehra reports receiving fees for serving as a clinical trial leader from Abbott, Medtronic, and Janssen, and advisory board fees from NuPulseCV, Portola, Bayer, and FineHeart. No other potential conflict of interest relevant to this article was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
281
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(290 citation statements)
references
References 20 publications
9
281
0
Order By: Relevance
“…Of our 6 viremic patients, there was evidence of significant posttransplant leukopenia in 5 (83%). Recent studies suggest a seroconversion rate of ~ 50% in recipients of HCV NAT + organs . It is worth noting that none of our 6 patients seroconverted despite persistent viremia.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Of our 6 viremic patients, there was evidence of significant posttransplant leukopenia in 5 (83%). Recent studies suggest a seroconversion rate of ~ 50% in recipients of HCV NAT + organs . It is worth noting that none of our 6 patients seroconverted despite persistent viremia.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, we theorized that at least in some cases the inoculum of donor virus might be small enough to enable spontaneous clearance or clearance with a short prophylactic course of DAA. It is important to note that we developed and initiated our study prior to detailed published results for the THINKER and EXPANDER‐1 studies and well before the study in heart and lung transplant recipients . We also took into account the pharmacokinetics of sofosbuvir in patients with end‐stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the introduction of new DAA treatments has considerably reshaped the landscape of HCV treatment, prompting a discussion about the optimal timing of HCV treatment and trade‐offs between pre‐LT and post‐LT treatment, given the potential for liver recovery . At the same time, the notion of donor‐derived HCV transmission in transplantation has also received a great deal of attention due to the possibility of significantly increasing the pool of transplantable organs . These findings highlight the importance of constantly updating the guidelines in the context of the rapidly changing landscape of HCV in LT.…”
Section: Discussionmentioning
confidence: 99%
“…Wooley et al conducted a single‐center, open‐label pilot trial of patients receiving organ transplantation from HCV‐infected donors of various genotypes (n = 44 with 36 lung and 8 heart transplants) who received 4 weeks of sofosbuvir and velpatasvir immediately after transplantation. The authors found that, on follow‐up, all 35 patients (100%) were alive with excellent graft function and undetectable viral load 6 months after transplantation . Further data are needed regarding outcomes associated with liver transplantation, as well as optimal treatment duration and timing.…”
Section: Hepatitis C: From Chronic Malady To Robust Curementioning
confidence: 99%